SISTEM PENGOLAHAN DATA SATELIT SERI NOAA JPSS UNTUK PRODUKSI INFORMASI TITIK PANAS SECARA OTOMATIS - Budhi Gustiandi; Donna Monica; Andy Indradjad (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2020)
The number of forest and land fires that were happened worldwide had been estimated to increase in the last years. Forest and land fires play a significant role in climate change because they are one of primary sources of carbondioxide and particulate matter that can affect chemical composition in the troposphere. To understand dynamics of forest and land fires in a wide scale, remote sensing satellite technology is considered as the most effective technique. Forest and land fires indicator products that are produced from remote sensing data processing are known widely as active fires or hot spots. A Joint Polar Satellite System generation 1 (JPSS-1) – also known as National Oceanic and Atmospheric Administration generation 20 (NOAA-20) – remote sensing satellite data processing system has been built to produce active fires or hotspots information automatically. The system is a development of existing Suomi National Polar-orbiting Partnership (Suomi-NPP) remote sensing satellite data processing system which is the predecessor of JPSS-1 / NOAA-20 satellite. System design, processing flow, and software used as parts of the system are elaborated in detail in this paper. Analysis of output products that are produced by the system are also described in detain in this paper. It is hoped that active fires or hotspots information products that are produced by the developed system can be utilized in national scale similar to their predecessor products that are produced by previous system, even they can be utilized in regional scale.